Kepustakawanan dalam "The Name of The Rose" karya Umberto Eco - Laksmi, Laksmi (Wacana, Journal of the Humanities of Indonesia, 2005)
The Name of the Rose, a detective novel, is set by some issues on librarianship during the Middle Age in Europe. By using discourse analysis approach, I try to know how far the concept of the librarianship was understood at that time-in the novel-based on the understanding of some concepts, starting from "library", "development system", "collection handling", which includes "classification", "censorship system" and "librarians' professionalism", until some matters on borrowing and using collection. Besides, this analysis is aimed at identifying cultural values related to the librarianship. The conclusion shows that the librarianship has an important role in providing suspense elements in a detective novel.